Images of Librarians Disclosed by means of Cartoons (Research, Society and Development, 2019)
Currently there are about 30,000 librarians in Brazil who work in information or documentation centers, university libraries, school libraries and others, and it is interesting to know the image that people in society have about librarianship professionals. The objective of this article is to present a research work in which one tries to reveal the image of common sense towards librarians, through cartoons. These at the same time that amuse themselves are also loaded with social representations. This study is an exploratory research, which is an initial research, in which information is sought in web cartoons trying to understand through them the common sense in relation to librarians. It turns out that the image of the professionals is good, it is associated with the female sex, it is linked to the information and people feel that the world would be better with more libraries. Thus, it is considered that the image favors the insertion of professionals in the context of libraries and, therefore, of formal and / or informal education.